TATO MENTAWAI DALAM KARYA LUKIS DEKORATIF - Drs. Erfahmi, M.Sn., Supriadi Saleleubaja, Dra. Jupriani, M.Sn., (Serupa The Journal of Art Education, 2017)
The purpose of the creation of this final work is visualize the tattoo motif in decorative painting. The method of creating artwork uses five stages: preparation stage, elaboration stage, synthesis stage, concept realization stage and completion stage. In the creation of works, use acrylic paint on canvas using black, reddish-brown and blue. The style used is a decorative style that is the flow of painting style that combines the lines and arches to form fields or objects. So the shape of objects in decorative painting tends to look like geomatrical fields. The tenth works are: 1) Dapdap, 2) Jekguk, 3) Muriok Sara, 4) Titi Rere, 5) Sibalu-balu, 6) Sikoinan Pay-pay, 7) Titi Bakkapat, 8) Durukat, 9) Titi Baylat , 10) Takep.Keywords: Mentawai Tattoos, Painting, Decorative